The random character of interest rates : applying statistical probability to the bond markets - Murphy, Joseph E. (London ; New York : McGraw-Hill, 1990)
Meant for bond traders, fund/portfolio managers, and individual investors, treasury officers, bankers, and investment advisors.
Includes bibliographical references (p. 313-316) and index.
gau 26/07/16
Loan
Keywords: Bonds markets; Interest rates; Bond market